Gender disparities in wage returns to human capital components: how different are European labour markets?. Issue 1 (2nd January 2022) - Tverdostup, Maryna; Paas, Tiiu
ABSTRACT: The paper investigates the gender wage gap in relation to the multi-dimensional human capital measure, asking which human capital components are most valued in the European labour markets. Relying on the Programme of International Assessment of Adult Competencies (PIAAC) data for seventeen European countries and applying Gelbach (2016 ) decomposition, we document remarkable cross-country disparities in the returns to different human capital components. The only dimension that consistently and significantly decreases gender wage disparities in all countries is work experience related to a currently occupied position. Numeracy cognitive ability is another strong predictors of the gender wage disparity, while job-specific cognitive and non-cognitive skills reveal weaker than expected association with the gender wage gap. Unlike the studies stressing the decreasing importance of human capital in the gender wage gap assessment, we argue that a narrow definition of human capital may undermine the actual effect of the latter.